The real consequences of financial stress - Stefan Mittnik; Willi Semmler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2013)
We introduce a dynamic banking-macro model, which abstains from conventional mean-reversion assumptions and in which - similar to Brunnermeier and Sannikov (2010) - adverse asset-price movements and their impact on risk premia and credit spreads can induce instabilities in the banking sector. To assess such phenomena empirically, we employ a multi-regime vector autoregression (MRVAR) approach rather than conventional linear vector autoregressions. We conduct bivariate empirical analyses, using country-specific financial-stress indices and industrial production, for the U.S., the UK and the four large euro-area countries. Our MRVAR-based impulse-response studies demonstrate that, compared to a linear specification, response profiles are dependent on the current state of the economy as well as the sign and size of shocks. Previous multi-regime-based studies, focusing solely on the regime-dependence of responses, conclude that, during a high-stress period, stress-increasing shocks have more dramatic consequences for economic activity than during low stress. Conducting size-dependent response analysis, we find that this holds only for small shocks and reverses when shocks become sufficiently large to induce immediate regime switches. Our findings also suggest that, in states of high financial stress, large negative shocks to financial-stress have sizeable positive effects on real activity and support the idea of unconventional monetary policy measures in cases of extreme financial stress.
Keywords: E2; E6; C13; 330; banking-sector instability; financial stress; monetary policy; nonlinear VAR; regime dependence; Bankenkrise; Finanzkrise; Geldpolitik; VAR-Modell; Theorie